Urea-Induced Enhancement of Hypocrellin A Synthesis in Shiraia bambusicola GDMCC 60438: Strategies and Mechanisms - Yanbo Tang; Yongdi Wen; Xiang Zhang; Qian Gao; Fuqiang Yu; Zhenqiang Wu; Xiaofei Tian (Fermentation, 2024)
Hypocrellin A (HA) is a valuable pigment with promising applications in biotechnology and pharmaceuticals. The submerged cultivation of Shiraia bambusicola offers a strategic opportunity to enhance HA production. This study investigates the regulatory mechanisms for HA biosynthesis through urea supplementation and presents a strategy to increase HA yield. In the absence of urea, S. bambusicola (GDMCC 60438) does not synthesize HA. However, the addition of 40 g/L urea 12 h into the fermentation process results in a final HA production of 46.7 ± 8.2 mg/L. Morphological analysis reveals an optimized environment for HA synthesis, characterized by a densely intertwined and reticular hyphal structure with minute pores. RNA sequencing shows significant upregulation of genes involved in DNA repair, recombination, and metabolism. Conversely, genes related to cellular homeostasis, cell-wall chitin, and amino polysaccharide metabolism are downregulated. Urea supplementation facilitates the upregulation of amino acid metabolism and the cysteine desulfurase gene, enhancing acetyl-CoA accumulation within the mycelium and providing the necessary precursor materials for HA synthesis. Our work underscores the pivotal role of urea in regulating HA biosynthesis and proposes a practical approach to enhance HA production. The findings contribute novel insights to the fields of biotechnology for pharmaceuticals.